2012
DOI: 10.1007/s10753-012-9444-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol Extract of Trigonella foenum graecum (Fenugreek) Seeds on Freund's Adjuvant-Induced Arthritis in Albino Rats

Abstract: Trigonella foenum graecum is an Iranian medicinal plant used for the treatment of rheumatoid arthritis and inflammation. The present study was designed to investigate the beneficial outcome of the plant T. foenum graecum on adjuvant-induced arthritis in albino rats. Ethanol extract of T. foenum graecum was tested against Freund's complete adjuvant-induced arthritis in rats. In the present study, paw volume was measured on the 4th, 8th, 14th and 21st day. On day 22, animals were anaesthetized, and blood samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 27 publications
0
67
0
Order By: Relevance
“…Diclofenac was chosen as a reference anti-inflammatory agent due to its proven anti-arthritic effects in Adjuvant-induced arthritis [27, 28]. Its selected dose is in accordance with previous literature [27, 28]. The chosen regimen is in accordance with previous reports [23, 29].…”
Section: Methodsmentioning
confidence: 99%
“…Diclofenac was chosen as a reference anti-inflammatory agent due to its proven anti-arthritic effects in Adjuvant-induced arthritis [27, 28]. Its selected dose is in accordance with previous literature [27, 28]. The chosen regimen is in accordance with previous reports [23, 29].…”
Section: Methodsmentioning
confidence: 99%
“…Literature frequently reported anti-inflammatory effects of fenugreek seed extracts (13, 25, 26). We thus tested the hypothesis that Stifenia could decrease the LPS-induced IL-1β production in PBMC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the body weight was regarded as an indirect index to evaluate the development of adjuvant-induced arthritis (Calvino et al, 1987;Chitme and Patel, 2009). The previous papers reported that a loss of body weight was observed during the arthritic process in an adjuvant-induced arthritis rat model (Walz et al, 1971;Suresh et al, 2012). The loss of body weight is due to the increasing severity of arthritis.…”
Section: Discussionmentioning
confidence: 96%